A GREAT POET, THINKER AND LITERARY FIGURE OF HINDI LITERATURE: SUMITRANANDAN PANT - Sharma, Mamta (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study is based on the life and literary contribution of Sumitranandan Pant, a leading poet of the Chhayavaad (Symbolism) movement in Hindi literature. Born in 1900 in Kausani village of Uttarakhand, Pant's poetic journey spanned almost six decades (1916-1977). His poetic development can be divided into three major phases: the first phase was of Chhayavaad poetry, the second phase was of progressive poetry influenced by Marxism and Freudism, and the third phase was inspired by spirituality and philosophical ideas. Pant's major poetry collections include Veena, Pallava, Yugantar, Chidambara, and Rajat Shikhar. He was awarded prestigious awards like Sahitya Akademi Award and Jnanpith Award. This study focuses on his poetic inclinations, intellectual influences and literary legacy. In addition, Pant's house has been converted into the 'Sumitranandan Pant Sahitya Vithika' museum in Kausani, where his personal belongings and handwritten manuscripts have been preserved. Through this study an attempt has been made to understand Pant's literary contribution and his wide-reaching influence.